Control of the amount and functionality of the eEF1A1 and eEF1A2 isoforms in mammalian cells - Negrutskii, B.S.; Novosylna, O.V.; Porubleva, L.V.; Vislovukh, A.A. (Вiopolymers and Cell, 2018)
Aim. To review mechanisms of regulation of expression and the functionality of two isoforms of translation elongation factor eEF1A in mammalian cells. Results. eEF1A1 and eEF1A2 proteins are regulated by post-translational modifications, protein-protein and protein-tRNA interactions as well as by controlling the amount of their mRNAs in human cells. Conclusions. EEF1A1 mRNA levels in cancer cells may depend on the allelic copy number while the level of EEF1A2 mRNA may be controlled by micro RNAs. eEF1A2 protein activity in different cellular processes may be determined, in part, by its increased affinity for tRNA and viral RNAs as compared to eEF1A1. eEF1A1 activity can be regulated by its increased susceptibility to post-translational modifications (PTM) and protein-protein interactions (PTI) as compared to eEF1A2.